2020
DOI: 10.15406/htij.2020.08.00215
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ABO blood groups in patients with haematological malignancies: a retrospective study

Abstract: Background: The pattern and distribution of Haematological malignancies vary depending on age, sex and geographical location. Studies on the association between Haematological cancers and ABO blood types have been largely conflicting. The objective of our study was to determine the distribution of ABO blood groups among patients with Haematological malignancies and to correlate with age and gender. Materials and Methods: This was a chart based observational descriptive study involving the review of records of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In addition to the physiological changes, the association between ABO BG antigens expression and erythropoiesis is known for carcinomas and hematological malignancies [ 32 , 56 58 ]. The association of reduction or complete deletion of A/B antigen expression with acute myeloid leukemia (AML), myelodysplastic syndrome (MDS) and myeloproliferative disorders including chronic myeloid leukemia is well documented [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the physiological changes, the association between ABO BG antigens expression and erythropoiesis is known for carcinomas and hematological malignancies [ 32 , 56 58 ]. The association of reduction or complete deletion of A/B antigen expression with acute myeloid leukemia (AML), myelodysplastic syndrome (MDS) and myeloproliferative disorders including chronic myeloid leukemia is well documented [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the loss of A, B or H antigens from the surface of RBCs can be seen in hematological malignancies. Thus, the loss of ABO BG antigens expression in an RBC population derived from a malignant HSC clone could be an indicator of genetic changes during oncogenesis on the stem/progenitor cell level [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for exploring ABO blood groups distribution and their possible association with ALL etiopathology, the majority of the patients were of the A-blood type while the AB blood group was the least common. In congruence, previous studies showed that the AB-blood group type in hematologic malignancies was the least common [ 83 , 84 ]. Other study showed that the most common blood group of leukemia patients was B [ 25 ].…”
Section: Discussionmentioning
confidence: 62%